A long-term survivor with esophageal melanoma and pulmonary metastasis after single-stage esophagectomy and lobectomy: Case report and literature review. Issue 21 (May 2017) - Zhao, Tian; Kong, Feng-Wei; Wang, Heng; Liu, Dong; Wang, Chun-Ying; Luo, Jin-Hua; Zhang, Miao; Wu, Wen-Bin
Abstract: Rationale: The optimal therapeutic regimen for primary malignant melanoma of the esophagus (PMME) need to be further elucidated. Besides, the efficacy of surgery for PMME with remote metastasis is uncertain for its rarity. Patient concerns: Herein a previously healthy patient was admitted for dysphagia and fatigue, without significant weight loss. Diagnoses: The pathological and molecular tests revealed his diagnosis of BRAF-mutant, advanced PMME with localized pulmonary metastasis. Interventions: Single-stage Ivor-Lewis esophagectomy and lobectomy were performed successfully, followed by 4 cycles of conventional chemotherapy, and concurrent high-dose interferon lasting for 1 year. Outcomes: The patient survived without logo-regional recurrence or remote metastasis during the follow up of two and a half years up to now. Lessons: Timely resection of localized primary and metastatic lesions might deliver a chance to obtain better prognosis for selected PMME patients; however, high-quality trials with longer follow-up are needed.